Analysis of the Implementation of Science Learning Methods in the Merdeka Curriculum at SMP Negeri 1 Jember - Arliantika, Saskia Safna; Zahir, Neza Luna; Hasbi, Upik Sahrun Nadifa; Asyahwa, Serina Khusana; Aditya, Muhammad Virga; Sumiati, Ika Dewi (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study was motivated by the low initial competence of students at the beginning of each new chapter in science learning. This situation often disrupts the teaching and learning process because teachers must repeat basic explanations before moving to the main material. If this continues, learning effectiveness will decline and objectives may not be achieved optimally. Therefore, it is important to understand how teachers respond to this issue through appropriate learning methods. The purpose of this study is to identify and describe the science learning methods used by junior high school teachers in addressing students’ low prior knowledge. This research uses a qualitative approach with a case study design. The subjects are science teachers at SMPN 1 Jember selected for their direct experience in teaching and handling classroom challenges. Data were collected through observations, interviews, and documentation to obtain a comprehensive picture of instructional practices. The findings show that teachers choose learning methods based on the characteristics of the material. Conceptual topics are taught through group discussions to encourage peer interaction, while practical material is delivered through experiments to strengthen hands-on skills. Interactive lectures are also used to introduce new concepts clearly. However, several challenges occur, including human error in classroom management, restrictions on mobile phone use that limit digital resource access, and low student participation. These issues highlight the need for more adaptive and innovative science teaching strategies